Insight into Out‐of‐Layer Fluctuations in the Smectic A Stability of 3, 5‐Diarylisoxazole Liquid Crystals. Issue 13 (3rd June 2020) - Sales, Eric S.; dos Santos, Gabriel M.; Mandle, Richard J.; Costa, Wallison C.; Bechtold, Ivan H.; Gonçalves, Itamar L.; Eifler‐Lima, Vera L.; Merlo, Aloir A.
Abstract: Polar‐terminated 3, 5‐diarylisoxazole liquid crystals (ILCs) were synthetized and characterized. ILCs are composed by rigid core 3, 5‐diarylisoxazol, alkyl chain and polar‐terminated flexible spacer. Hydroxyl‐, ketal‐ and 1, 2‐diol‐terminated ILCs rendered smectic C and A mesophase, while bromine‐terminated ILCs showed smectic A and B mesophase, for monosubstituted and linear ILCs. For branched alkyl chain monotropic SmA was detected and for disubstituted ILCs no mesophase was detected. Out‐of‐layer fluctuations (OLFs) are discussed based on X‐ray diffraction date and textures. The OLFs are dependent on the bromine atom hardness, hydrogen bonding through collective actions and conformational effects at the interface between layers. Smectic translational order parameter (TOP) Σ was also obtained for orientated bromine‐ and hydroxyl‐terminated ILCs and related it with OLFs. For 1, 2‐diol‐terminated ILCs two SmC sublayers were founded, probably related to the intramolecular hydrogen bond favoring the 5‐membered and 6‐membered formation. Abstract : Out‐of layer fluctuations are turbulences at the interface of layered liquid crystals driven by intermolecular interactions. Instabilities of the interface in an SmA mesophase are analyzed by X‐ray diffraction. For hydroxyl‐terminated isoxazole liquid crystals (ILCs), the sequence SmA to SmC mesophase is favored by lateral diffusion, while longitudinal diffusion favors the sequence SmA to SmB mesophase for bromine‐terminated ILCs.